Long basal height character, its inheritance and utility in breeding for plant architecture in dry beans - Alberini, João Luiz; Tara Mohan, S. (Pesquisa Agropecuaria Brasileira, 2014)
A spontaneous mutant with basal height (Height of epicotyl + hypocotyl) three times longer than normal was observed in the field planting of a commercial bean variety (Phaseolus vulgaris L.). The inheritance studies revealed that this character is under the control of a single recessive gene which is designated a gene symbol "Mia" (Mutante inserção alta). By the virtue of the long basal height, the height of pod insertion is also increased, thus avoiding the contact of the pods with the soil, which can be of value in maintaining the high seed quality. The crosses of this line with commercial varieties resulted in several promissory selections to be tested for their suitability for mechanical harvest.